A case of persistent fever, cutaneous manifestations and pulmonary and splenic nodules: clinical experience and a literature review. Issue 2 (12th February 2019) - Xu, Ping; Cai, Yazhou; Ying, Xiaona; Shi, Shiqiao; Song, Weidong
Abstract: Pyoderma gangrenosum (PG) is a rare and recurrent ulcerating, non‐infectious, inflammatory dermatosis, with occasional concomitant extracutaneous manifestations. The pathogenesis and aetiology of PG are unknown. Moreover, early diagnosis is challenging because there are several visceral manifestations that may occur prior to the skin findings, such that misdiagnosis of PG as an infection is common. Here, we present a case of PG in which pulmonary and spleen lesions preceded the cutaneous manifestations. The correct diagnosis was made 6 months after multiple nodules were detected in the lung and spleen, based on the development of skin wound ulcers. To the best of our knowledge, this is the first report of PG in which pulmonary and splenic involvement preceded the appearance of skin lesions, without systemic disease. The patient was followed up for 5 years, during which time complete clinical and radiographic resolution was confirmed. This case demonstrates the challenges in the diagnosis of PG and the importance of using multiple diagnostic methods to determine the cause of unexplained clinical manifestations.